Kegiatan Penyuluhan 4 Sehat 5 Sempurna SD MI Amiroh Jakarta - Salman naning; Mira Ziveria (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2022)
Food for 4 healthy 5 perfect is a lifestyle that has been done by some people. The habit of eating healthy food in the future will help the community, especially children, to grow up happy and healthy and be a form of contribution to preventing health problems in the future. This 4 healthy 5 perfect food campaign then became the basis of the implementation of the PKM program with the title